War, displacement and the making of a new social class: an ethnographic study on Afghani refugees in Manhattan, Kansas - Amin, Ruhul (My University, 2024)
Abstract: This oral history project intends to register the life history and the working experience of a group of people who are idiosyncratic in world history. In my project, I refer to this group as the Naway Maldar people: these are people who quickly became affluent and influenced the Afghani state, emerging in the context of the American-led war on terror in Afghanistan. Two distinctive phenomena contributed to the emergence of the Nawya Maldar people. Firstly, the flow of Western money which created high-paying jobs; secondly, the presence of the Western, especially American, military under which this new social class I refer to as the Naway Maldar could flourished. Fluency in several Western languages, most notably English, helped the Naway Maldar people get high-paying jobs. These jobs made them a distinctive social class in the post 9/11-era in Afghanistan, but also isolated them from the Afghani traditional life and disrupted their familial relationships and kinship with their countrymen. This oral history project also intends to register how the Naway Maldar people were subjected to violence from their own people due to their associations with Western NGOs and the American administration in Afghanistan. These experiences of violence left a lifelong trauma in many of the Naway Maldar people. The high-paid jobs attained by the Naway Maldar people depended on the presence of the American military. For this reason, when Americans started to leave Afghanistan, the Naway Maldar people and their consumption-based life started to decay. Many of them were rescued from dire situations in Afghanistan and settled across the United States. Lastly, this project intends to register the predicament of the post-evacuation life of the Naway Maldar in Manhattan, Kansas.
Keywords: War; Displacement; Social class; Afghan refugees